Migration and Social Distance: Various ethnic groups as perceived by the Ural’s schoolchildren and their parents - Kuzmin, Konstantin; Petrova, Larisa; Popov, Dmitriy (International Dialogues on Education Journal, 2015)
The article is an overview of an empirical study, conducted in 2012-2013, of social distance between various ethnic groups in the Sverdlovsk District (oblast), Russia. Using an adapted form of the Bogardus scale we analyzed attitudes toward major ethnic groups in the region through the generational prism of local children and their parents. The personal migration experiences of respondents and the age of schoolchildren are seen as important and differentiating features in people’s attitudes toward ethnic minorities.